Receiving Erin : Philadelphia, Liverpool, and the Irish Famine Migration, 1845-1855. - Gallman, J. Matthew (University of North Carolina Press, 2000)
During the Irish famine 2,000,000 Irish men and women fled their homeland to settle in large British and American cities already wrestling complex urban problems. This book examines how the cities of Liverpool and Philadelphia met the challenge of this influx of immigrants.